As aves do estado do Maranhão: atualização do conhecimento e conservação em uma região de ecótono entre a floresta Amazônica e Cerrado - CARVALHO, Dorinny Lisboa de (Universidade Federal do Pará, 2019)
The state of Maranhão is located between the eastern Amazon and the northern Cerrado, presenting a wide variety of environments in its ecotonal area. Due to this environmental heterogeneity, Maranhão has one of the richest avifaunas in Brazil. Furthermore, this region includes one of the world's most endangered biogeographical provinces. In order to contribute to the knowledge and conservation of avifauna in this region, this study has as its main objectives: 1) review and update the checklist of birds species from Maranhão to identify possiblesampling gaps in the state; 2) test the effectiveness of the State Protected Areas (PAs) and Indigenous Lands (TIs) system in the protection of threatened and endemic bird species using SDMs and; 3) assess the potential impact of climate change on the distribution and conservation of 24 threatened bird taxa occurring in the state, comparing current and future distributions (2070) with the current reserve system, in order to identify potentially stable areas that can serve as dispersal corridors for the evaluated taxa. In chapter 1) we recorded the occurrence of 750 bird species, distributed into 88 families and 30 orders. We added 114 new species (95 residents, 13 migratory and 6 vagrants) to the last list compiled 27 years ago for the same region. In chapter 2) we observed that taxa with wider distributions are protected equally as taxa with smaller distributions and larger PAs are more efficient than smaller. Our results also showed that most Cerrado PAs are poorly allocated. We suggest six priority areas for conservation of Neotropical birds and highlight the importance of indigenous lands in conserving Neotropical biodiversity. In chapter 3) our results indicated that, although threatened Amazon and Cerrado taxa are potentially protected, for both present and future scenarios, most of the taxa are likely to suffer drastic population size declines or even global extinction in the near future. We highlight the importance of creating a system of dispersal corridors that interconnect PAs in this region, as well as the implementation of public policies for maintenance and mitigation of the areas adjacent to these corridors, aiming at the conservation of the richness and diversity of species in this region.